2017
DOI: 10.1111/cogs.12476
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Anchoring Model: How Static and Dynamic Presentations of Time Series Influence Judgments and Predictions

Abstract: When attempting to predict future events, people commonly rely on historical data. One psychological characteristic of judgmental forecasting of time series, established by research, is that when people make forecasts from series, they tend to underestimate future values for upward trends and overestimate them for downward ones, so‐called trend‐damping (modeled by anchoring on, and insufficient adjustment from, the average of recent time series values). Events in a time series can be experienced sequentially (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 61 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…20 A variant it to use exponentially-decreasing weights. If the number is Kusev et al (2018) make further progress in modeling anchoring on linear or other non-exponential approximations in the context of subjective time-series forecasting. all this.…”
Section: Taking Stock Of These Examplesmentioning
confidence: 99%
“…20 A variant it to use exponentially-decreasing weights. If the number is Kusev et al (2018) make further progress in modeling anchoring on linear or other non-exponential approximations in the context of subjective time-series forecasting. all this.…”
Section: Taking Stock Of These Examplesmentioning
confidence: 99%
“…It is also well established that human agents experience decision-making information rather than relying on descriptions of decision-making information. For example, risky events in the real world are experienced sequentially and often without contextual summaries ( Hertwig et al, 2004 ; Stewart et al, 2006 ; Kusev et al, in press ). However, some risky events are not experienced individually over time, but are reviewed retrospectively and can also immediately be inspected holistically as with learning about decisions from descriptions ( Tversky and Kahneman, 1992 ).…”
Section: How Do Cognitions and Emotions Influence Risky Behaviormentioning
confidence: 99%
“…Additionally, we believe that the effect of presentation formats on priors in time series data should also be assessed. For example, Kusev, van Schaik, Tsaneva-Atanasova, Juliusson, and Chater (2018) showed that presenting time series data sequentially instead of revealing all of the points at once improved the accuracy of participants' forecasts but did not have an effect on their estimations of the mean.…”
Section: Future Workmentioning
confidence: 99%